Comparison of Negative Pressure Wound Therapy and Silver-Coated Foam Dressings in Open Wound Treatment in Dogs: A Prospective Controlled Clinical Trial - Nolff, Mirja C.; Albert, Rebecca; Reese, Sven; Meyer-Lindenberg, Andrea (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives To evaluate negative pressure wound therapy (NPWT) for treatment of complicated wounds in dogs.Study Type Prospective randomized clinical studyMaterials and Methods Dogs (n = 26) undergoing open-wound treatment were randomly assigned to one of two groups: Group A (n = 13) NPWT; Group B (n = 13) silver-coated foam dressing. Pairs of patients were matched based on wound conformation, localization, and underlying cause and compared in terms of duration of previous treatment, development of wound size (wound planimetry), time to closure, bacterial bio-burden and complications. Wound dressing changes were performed every 3 days during the first 9 days of therapy for both groups. Statistical analysis was performed.Results Pre-treatment signalment and bacterial status were comparable between groups. Total time to closure was significantly (p = 0.018) shorter in Group A (14.2 days) compared with Group B (28.6 days), and wound planimetry on days 3, 6 and 9 showed significant greater reduction in total wound area for Group A at all-time points (p < 0.05). Furthermore, wounds in Group A showed less progression of local infection than did wounds in Group B (p = 0.01).Conclusion NPWT-treated wounds showed faster closure, improved macro-deformation and less local signs of infection.
Keywords: negative pressure wound therapy; polyurethane foam; wound bioburden; open wound management; wound; wound planimetry; dog